Prototyping Behavioural Specifications in the.NET framework - F. Rodrigues, Nuno (2013)
Over the last decade, software architecture emerged as a critical design step in Software Engineering. This encompassed a shift from traditional programming towards the deployment and assembly of independent components. The specification of the overall system structure, on the one hand, and of the interactions patterns between its components, on the other, became a major concern for the working developer. Although a number of formalisms to express behaviour and supply the indispensable calculational power to reason about designs, are available, the task of deriving architectural designs on top of popular component platforms has remained largely informal. This paper introduces a systematic approach to derive, from behavioural specifications written in Ccs, the corresponding architectural skeletons in the Microsoft .Net framework in the form of executable C] code. Such prototyping process is automated by means of a specific tool developed in Haskell